Peningkatan Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik Menggunakan Model Pembelajaran Project-Based Learning (PjBL) Materi Tata Surya Kelas 6A di SDN 05 Cakranegara - Humaidi, Hilman; Sujana, I Made; Taufiqurrahman, Irwan (Mataram University, 2025)
The problem underlying this research is the low conceptual understanding and learning outcomes of students on the topic of the Solar System, as well as the learning process that remains teacher-centered and lacks active student engagement. Based on the preliminary study, out of 21 students in class 6A of SDN 05 Cakranegara, only 6 students (29%) achieved the Minimum Mastery Criteria (KKM), while 15 students (71%) did not. This study aims to describe the implementation of the Project-Based Learning (PjBL) model in improving students’ learning outcomes and critical thinking skills. The research employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, consisting of two cycles. Research instruments included learning outcome tests, student activity observation sheets, and student perception questionnaires. The results showed a significant improvement in all learning indicators. Teacher and student activities increased from a score of 31 (70% – Fair) in Cycle I to 41 (93% – Excellent) in Cycle II. The implementation of the PjBL learning syntax also improved, from a score of 5 (83% – Good) in Cycle I to 6 (100% – Excellent) in Cycle II. Students’ critical thinking skills increased from 781 (67% – Poor) in Cycle I to 966 (83% – Good) in Cycle II. The most significant improvement was observed in students’ learning outcomes, with the average score rising from 75 (68% – Fair) in Cycle I to 88 (90% – Excellent) in Cycle II. Therefore, it can be concluded that the implementation of the Project-Based Learning (PjBL) model is effective in enhancing students’ learning outcomes and critical thinking skills on the topic of the Solar System in Grade VI A of SDN 05 Cakranegara.